O efeito da carga normal no comportamento tribológico de uma superliga de cobalto no ensaio pino-disco - Tauffer, Renato Leão (2014)
It has been reported in the literature that the wear and the friction coefficient (μ) in sliding wear tests of cobalt-base alloys is strongly influenced by the phase transformation (FCC to HCP) that takes place in these alloys due to mechanical work. Usually the values of μ, after the transformation, are in the range of 0.15-0.20. The present work reports the behavior of friction and wear for the unlubricated sliding of a supermartensitic stainless steel pin on an as-cast Co-base superalloy disk, using a PLINT TE-67 tribometer. The tests were conducted at room temperature, using a single sliding speed and varying the normal load (5-500 N). The coefficient of friction and the contact potential were monitored during the tests. Scanning electron microscopy (SEM) and 3D profilometry were used to characterize the wear volume and wear mechanisms. For loads ranging from 350 to 450 N, after achieving steady-state conditions, an unusual very low friction coefficient (μ<0.01) and low wear rate were found. The X-ray diffraction analysis on the wear track revealed the mentioned transformation.